Experimental investigation on density, kinematic viscosity and calorific value of sunflower oil - pentanol binary biofuel blend - Sharudin, Hazim; Che Mat, Sharzali; Nazri, Nur Irsalina Huda; Ab Hamid Pahmi, Muhammad Arif; Husin, Azmi; Ismail, Noor Iswadi; Mahamad Basri, Mahamad Hisyam; Othman, Rozaini (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
The usage of fossil fuels as the main energy source has become a serious problem due to concerns over environmental pollution and the rising fuel prices worldwide. Straight Vegetable Oil (SVO), such as Pure Sunflower Oil (PSO), is a possible alternative biofuel to petroleum diesel fuel because of its physical qualities identical to fossil fuel. However, the higher viscosity and density of SVO limit its direct use in combustion engines, which will cause problems such as incomplete combustion and carbon deposits in the chamber due to the high viscosity and density. This work presents an experimental investigation to determine and soptimise the key properties of the Sunflower oil-Pentanol blend, which has the potential to be used to replace the existing fossil fuel. This study proposes a binary biofuel blend of Pure Sunflower Oil (PSO) with higher alcohol Pentanol (PEN). Design-Expert software is used to formulate, optimise, and predict the key properties of this binary biofuel blend. Based on mixture design analysis, a total of 8 blend ratios were obtained, which are 100PSO, 50PSO50PEN, 100PSO, 75PSO25PEN, 100PEN, 50PSO50PEN, 100PEN, and 25PSO75PEN. The developed model and experimental data for the density, kinematic viscosity, and calorific value models all yielded good results, with R² values of 0.9999, 1.0000, and 0.9949, respectively. All these responses meet the ASTM D6751 requirements for biodiesel and are suitable for use in a compression-ignition engine.